Musical learning for children with cerebral palsy: practices and needs - Moreno, Davys (2021)
In Portugal, educational inclusion is considered fundamental, as advocated by the Basic Law of the Educational System, Law Nº 46/86, Diário da República of 14 October, and Decree Laws Nº 344/1990 of 2 November and Nº 54/2018 of 6 July. However, when the mother of a child with Cerebral Palsy went to an Artistic School to enrol her 7-year-old child, in the first year of the First Cycle of Arts education programmes in music, she considered that the necessary conditions were not met so that the child could attend this type of education and ended up giving up the enrolment. Due to this reason and in order to promote the inclusion of children with Special Needs in Arts education programmes of music, in the year 2018 we began an action-research project. To this end, it has already been carried out: an initial awareness training for music education teachers; the characterization of the child who gave rise to the study and; an integrative literature review to know the state of the art in this area. As a result of this work there emerged the need to highlight the needs of parents and professionals who work with children with Special Needs. To this end, interview scripts were prepared and validated by professional experts in the areas of technology, music education, school inclusion and health. Using these scripts, between the months of November and December 2019 and November and December 2020, we interviewed 18 music professionals and 18 parents of children with Cerebral Palsy. These interviewees authorised the recording in audio format and the processing of their interviews through informed consent. The interviews were subsequently transcribed in Word and their transcription validated by the respective interviewees. All the compiled information was organized and studied through content analysis supported by software in the webQDA platform. The results obtained show that teachers are not yet prepared for the challenges posed by inclusion in Arts education programmes of music. Thus, they highlight the need for specific training, focused on the use of Technologies and Assistive Technologies, involving the educational community in an active and collaborative way. This does not dispense with the need for human resource support for all the needs of children with Special Needs, including basic needs. It will thus be possible to stimulate the potential of children with Cerebral Palsy to transform Artistic Music Education into Inclusive Education.